2001
DOI: 10.1128/aem.67.6.2603-2609.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inoculation and Leaf Litter Amendment on Establishment of Nodule-Forming Frankia Populations in Soil

Abstract: High-N 2 -fixing activities of Frankia populations in root nodules on Alnus glutinosa improve growth performance of the host plant. Therefore, the establishment of active, nodule-forming populations of Frankia in soil is desirable. In this study, we inoculated Frankia strains of Alnus host infection groups I, IIIa, and IV into soil already harboring indigenous populations of infection groups (IIIa, IIIb, and IV). Then we amended parts of the inoculated soil with leaf litter of A. glutinosa and kept these parts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…Frankia spp. are known to survive and remain infective in soil devoid of host plants (Nickel et al, 2001;Ridgway et al, 2004). Nonetheless, these results indicate good performance of Frankia-nodulated alders in OSPM and that planting alders to improve soil characteristics is a viable approach to enhance revegetation.…”
Section: Discussionmentioning
confidence: 92%
“…Frankia spp. are known to survive and remain infective in soil devoid of host plants (Nickel et al, 2001;Ridgway et al, 2004). Nonetheless, these results indicate good performance of Frankia-nodulated alders in OSPM and that planting alders to improve soil characteristics is a viable approach to enhance revegetation.…”
Section: Discussionmentioning
confidence: 92%
“…In our previous analyses, only one group of frankiae, i.e., subgroup II of the Alnus host infection group represented by strain Ag45/Mut15, was detected by qPCR in both nodules on A. glutinosa and in soils, though with numbers in soils that corresponded largely to those retrieved for nitrogen-fixing frankiae [19]. This subgroup was dominant apparently independent of environmental characteristics such as organic matter content and matric potential that had been shown to affect the development of specific Frankia populations [9][10][11]31]. Our current analyses detected three of our four target subgroups within the genus demonstrating the potential of our qPCRbased quantification procedure for population analyses in soils.…”
Section: Rbwmentioning
confidence: 93%
“…In the absence of plants, amendment of soils with slowly available C resources such as leaf litter affected the nodulation capacity of different Frankia strains [11] and allowed growth of a small number of strains only, all of which belonged to a distinct phylogenetic cluster within the Alnus host infection group [9,10]. Casuarina-infective strains, another distinct phylogenetic cluster within the Alnus host infection group [12,13], also grew saprotrophically, however, only in the rhizosphere of their host plant [10] or with leaf litter of Casuarina sp.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests that active Frankia populations in the soil may be preferentially selected by the host for nodulation (33,36). Previous research in our laboratory has confirmed the importance of the plant host in selecting Frankia strains for symbiosis when the same soil was inoculated into six different actinorhizal plant species and resulted in six different diversity profiles (34).…”
mentioning
confidence: 65%